Ligament and Droplet Generation by Oil Film on a Rotating Disk. (12th October 2015) - Sun, Hengchao; Chen, Guoding; Wang, Li'na; Wang, Fei
Abstract : The lubrication and heat transfer designs of bearing chamber depend on an understanding of oil/air two-phase flow. As initial and boundary conditions, the characteristics of ligament and droplet generation by oil film on rotating parts have significant influence on the feasibility of oil/air two-phase flow analysis. An integrated model to predict the oil film flow, ligament number, and droplet Sauter mean diameter (SMD) of a rotating disk, which is an abstraction of the droplet generation sources in a bearing chamber, is developed based on the oil film force balance analysis and wave theory. The oil film thickness and velocity, ligaments number, and droplet SMD are calculated as functions of the rotating disk radius, rotational speed and oil volume flow rate and oil properties. The theoretical results show that the oil film thickness and SMD are decreased with an increasing rotational speed, while the radial, transverse velocities, and ligament number are increased. The oil film thickness, radial velocity, and SMD are increased with an increasing oil flow rate, but the transverse velocity and ligament number are decreased. A test facility is built for the investigation into the ligament number of a rotating disk, and the measurement of ligament number is carried out by means of a high speed photography.